The Economics and Policy of Biomethane: A Pragmatic Approach to Renewable Energy and Waste Valorization - D’Adamo, Idiano; Fuoco, Matteo; Gastaldi, Massimo; Lupi, Barbara (International Journal of Energy Economics and Policy, 2025)
Biomethane, also known as green gas, contributes to urban sustainability and decarbonisation by valorising waste such as the Organic Fraction of Municipal Solid Waste (OFMSW). This study assesses the economic feasibility of a biomethane plant, using discounted cash flows in a medium-sized plant located in Rome using OFMSW as a substrate. The results confirm the project’s feasibility, with the following key indicators: a Net Present Value (NPV) of 1635 k€, an Internal Rate of Return of 46%, and a Discounted Payback Time of 3 years. Subsidies account for approximately 60% of revenues and therefore have a significant impact on the project’s economic viability. It emerges that at an incentive of 0.732 €/m3, the NPV is positive in 86% of simulated cases; if reduced to 0.627 €/m3, the probability of profitability drops to 27%. Break-even is reached at 0.623 €/m3 for a 250 m3/h plant. Stability of incentives and the development of a national supply chain are essential to ensure pragmatic and long-term sustainability and reduce reliance on public support. Biomethane supports SDGs 7-12 by providing renewable energy, promoting a circular economy, improving waste management, and contributing to more sustainable and inclusive cities.